S100 and Pan-Trk Staining to Report NTRK Fusion-Positive Uterine Sarcoma: Proceedings of the ISGyP Companion Society Session at the 2020 USCAP Annual Meeting. (January 2021) - Chiang, Sarah
Abstract : NTRK fusion-positive uterine sarcoma is a recently recognized mesenchymal tumor that is defined by its morphologic resemblance to soft tissue fibrosarcoma, NTRK gene rearrangements, and potential response to Trk inhibition. Reported lesions affect premenopausal women with a median age of 32 yr, and most arise in the uterine cervix. Haphazard, storiform, or herringbone patterns of spindle cells with mild to moderate nuclear atypia are characteristic. SMA, CD34, and S100 are variably positive, but tumors are negative for desmin, ER, PR, and SOX10 and retain H3K27me3 expression. While pan-Trk immunohistochemistry is positive in these tumors, it has decreased sensitivity and specificity in the evaluation of sarcomas in general and the detection of NTRK3 rearrangements. A variety of molecular methods such as fluorescence in situ hybridization and next-generation sequencing may be useful in confirming NTRK fusion in fibrosarcoma-like uterine sarcomas.